A Stable but Highly Reactive Phosphine‐Coordinated Borenium: Metal‐free Dihydrogen Activation and Alkyne 1, 2‐Carboboration1. Issue 19 (20th March 2015) - Devillard, Marc; Brousses, Rémy; Miqueu, Karinne; Bouhadir, Ghenwa; Bourissou, Didier
Abstract Borenium cations have been found to be valuable analogues of boranes as a result of their cationic character which imparts high electrophilicity. Herein, we report the synthesis, characterization, and reactivity of a new type of borenium cation employing a naphthyl bridge and a strong intramolecular P→B interaction. The cation reacts with H2 in the presence of PtBu3 (frustrated Lewis pair (FLP) approach) but also on its own. The mechanism of the reaction between the borenium cation and H2 in the absence of PtBu3 has been investigated using deuterium‐labeling experiments and DFT calculations. Both experiments and calculations imply the side‐on coordination of H2 to the B center, followed by heterolytic splitting and BC bond cleavage. An uncommon syn 1, 2‐carboboration has also been observed upon reaction of the borenium ion with 3‐hexyne.